THE INFLUENCE OF RELEASING CARBON EMISSIONS ON ACCOUNTING RETURNS: THE MODERATING ROLE OF BUSINESS STRATEGY - Pipin Kurnia; Supriono; Desmiyawati; Farid Artur Febrian; Rahmat Fajri (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study uses 1856 data from non-financial companies listed on the Indonesia Stock Exchange between 2015 and 2023 to examine business strategy as a modulator of the impact of carbon emissions disclosure on accounting returns. The relationship between creative business tactics and the disclosure of carbon emissions on accounting returns is what makes this study distinctive. Principal component analysis (PCA) is used for determining the value of the accounting functions. The study's findings suggest that business techniques mitigate the impact of disclosing carbon emissions on a company's accounting returns. This study contributes to regulations by showing that most non-financial companies are still not fully aware of the impact of climate change and that carbon emission disclosure is closely related to environmental pollution. As a result, the government needs to pay close attention to this issue. Companies must implement innovative business strategies by making carbon emissions disclosure a competitive advantage to increase the company's accounting return. In addition, this can also provide positive information to investors, thereby assisting investors in making investment decisions.